ID: 141. Issue 1 (November 2015) - Ziegler, Susanne M.; Beisel, Claudia; Hildebrandt, Heike; Gibbert, Kathrin; Griesbeck, Morgane; Altfeld, Marcus
<x xml:space="preserve">Abstract</x> The outcomes of many diseases differ between women and men, with women having a higher incidence and more severe pathogenesis of autoimmune and some infectious diseases, including influenza and HIV-1. In HIV-1 infection, clinical studies have shown faster disease progression and stronger immune activation in females compared to males for the same level of viral replication, as well as better control of initial viremia in women during primary infection (Meier, 2009; Sterling, 2001; Farzadegan, 1998). It has been suggested that this is partially due to TLR-mediated activation of pDC, the main producers of IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kff" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>, in response to HIV-1 ssRNA. We investigated the induction of type I interferons upon TLR7/8 stimulation on sorted pDC. PBMCs were stimulated for 2 h with a synthetic TLR7/8 ligand. pDC cells were isolated by flow-based sorting and subsequently mRNA was isolated. qRT-PCR revealed a sex-specific differential expression of type I Interferons, with pDC from females showing a higher expression level of corresponding interferons compared to males, including all IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kff" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>-subtypes (p = 0.003), as well as type III Interferons (IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7n52" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />λ</alternatives>1 p = 0.03). Of note, pDCs from females also showed higher IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7r0v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> expression (p = 0.059), which is part of the initial wave of gene transcription that triggers a positive feedback loop, leading to the induction of additional IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kff" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives>-encoding genes. These data demonstrate that sex-specific differences described in response to HIV-1 are associated with enhanced expression of several Interferons, with IFN<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7r0v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> being potentially responsible for the initiation of differential type I Interferon production between males and females.